Combined hypolipidemic therapy in patients who failed to achieve target values of the lipidogram. Possibilities of ezetimibe - N. V. Fedorova; V. V. Kashtalap; I. A. Shibanova; O. L. Barbarash (Лечащий Врач)
Clinical cases of effective use of combined lipid-lowering therapy (statin and ezetimibe) in patients with extremely high risk, who failed to achieve the target values of the level of low-density lipoprotein cholesterol were presented. Use of this drug combination allowed to achieve the target values of lipid spectrum in patients safely and effectively, and to reduce the risk of repeated cardiovascular events.